Developing a new green ship approach for flue gas emission estimation of bulk carriers - Bilgili, Levent; Celebi, Ugur Bugra (ELSEVIER SCI LTD, 2018)
Shipbuilding industry and shipping sector comprise of various complex production and operating processes, which consist of manufacturing, operation, repair/maintenance, scrapping/dismantling/recycling. Operation phase is the main source for production of various atmospheric contaminants. In the latest report of IMO, it is estimated that shipping activities are responsible for 2.2% and 2.1% of global CO2 and GHG emissions CO2 equivalent (including CH4 and N2O), which correspond to 35,640 and 39,113 million tons, respectively. IPCC estimates that the total fuel consumption will increase by 43.5% in 2050, at best. In this study, it is aimed to develop some equations in order to estimate the potential airborne emissions of a bulk carrier based on two main characteristics (DWT and C-B) during pre-design. For this purpose, the three-year operation data of nine bulk carriers are examined and a regression analysis was applied to obtain the equations.
Keywords: Ship emissions; Green ship; Emission estimation; Life cycle assessment; Regression analysis; TRAFFIC EXHAUST EMISSIONS; TURBINE COMBINED CYCLES; UPDATED EMISSIONS; AIR-POLLUTION; COASTAL WATERS; PRIME MOVERS; NORTH-SEA; PORT; MODEL; INVENTORIES; Engineering; Instruments & Instrumentation